STUDY ON THE EFFECT OF THE VITAMIN AND MINERAL COMPLEX CONTAINING ZINC L-ASPARTATE ON THE PERIODONTAL CONDITION OF RATS IN THE PRESENCE OF PERIODONTITIS MODELING - Schnaider, S.A.; Balega, M.I.; Zombor, Ye.V.; Semenov, Ye.I.; Tkachenko, Ye.K. (World of Medicine and Biology, 2020)
The purpose of the study was to study the effect of the vitamin and mineral complex containing zinc L-aspartate on the state of the periodontal tissues of rats under conditions of modeling periodontitis using exogenous collagenase. The vitamin and mineral complex containing zinc L-aspartate had a positive effect, to a greater extent, on the periodontal bone tissue. The complex has shown periodontal protection, anti-inflammatory, antioxidant properties.